Study of unsuspected gamma ray energy peaks observed during the determination of the half-life of activated aluminium - Nel, Andre Pierre (Department of Electrical Engineering, 2019)
In the experimental determination of the half-life of the decay of a radioactive element, an aluminium cylinder is activated through immersion in a thermal neutron bath. The decay of the irradiated aluminium cylinder is then measured to determine the half-life of the resultant 28Al. During the execution of the experiment, unsuspected gamma ray peaks other than the expected 1.78 MeV from the decay of the activated 28Al are however observed. Two potential hypotheses are considered in the study. The first hypothesis is that the 27Al from which the aluminium cylinder is manufactured is not pure and contains certain impurities which could be activated resulting in the measurement of the decay of materials other than the intended 28Al. The second hypothesis is the inadequate moderation of the neutrons resulting in the interaction of fast neutrons with the aluminium cylinder and hence the creation of something other than the intended 28Al. Based on the results of the two experiments conducted, it has been demonstrated that there is some evidence, though not very convincing, that both postulated hypotheses potentially hold true. Considering the relatively small amounts of alloying elements in a typical aluminium sample and the poor correlation between published half-lives with the derived half-lives from the experiment, the hypothesis that the impurities in the aluminium from which the aluminium cylinder is manufactured are activated when immersed in the neutron bath resulting in the measurement of the decay of materials other than the intended 28Al, is considered possible but improbable. On the other hand, considering the pertinence of the decay signature of 27Mg in both experiments, the observed increase in the 27Mg activity in the unmoderated activation, the abundance of the target nuclei of 27Al, as well as the increase in the 27Al (n,p) 27Mg reaction with increased neutron energy, hypotheses 2 is deemed both possible and probable.